Study of interfacial bonding properties and shrinkage deformation of cement-alkali activated gradient-structured composite in complex environments with temperature-humidity changes - Li, Xinzhe; Jiang, Ganyou; Wang, Naishuang; Wei, Yisong; Chen, Zheng; Li, Jing; Chen, Ben; Yu, Jiamin (Frontiers in Materials, 2025)
The early shrinkage-deformation and mechanical property evolution of gradient-structured composites in extreme environments are still insufficient. The paper prepared ordinary Portland cement-alkali-activated slag (OPC-AAS) and ordinary Portland cement-alkali-activated metakaolin (OPC-AAMK) gradient-structured composite by stacking cement and alkali-activated materials together. The effects of temperature difference cycling and wetdry cycling extremes on the early shrinkage strain and splitting strength of OPC-AAS and OPC-AAMK composites, as well as the structure of the bond interface and the micromorphology of the hydration products, were comparatively analyzed. The results demonstrated that the temperature difference cycling affected the early deformation and bond strength of the gradient-structured composite interfaces more significantly than the dry-wet cycling. The maximum expansion strains of OPC-AAS and OPC-AAMK were 1,130.88 μm and 1,399.25 μm, respectively, under the effect of temperature difference cycling; the splitting strengths of OPC-AAS and OPC-AAMK after three cycles of temperature difference cycling were reduced by 26.37% and 31.32%, respectively, compared with that after three cycles of wet-dry cycling. In addition, the OPC-AAS composites showed better interfacial bonding properties after extreme environmental cycling compared to the OPC-AAMK composites. The early splitting strengths under the two extreme environmental effects increased and then decreased, and the maximum splitting strengths of OPCAAS were 2.66 MPa and 3.65 MPa under the temperature difference cycling and dry-wet cycling, respectively, which were 5.14% and 35.69% higher than those of OPC-AAMK, respectively. Scanning electron microscopy (SEM) characterization analysis showed that the temperature difference cycling resulted in more severe product decomposition of the AAMK cementitious material, and obvious cracks and holes appeared at the bonding interface of OPC-AAMK. This study provides some references for the optimal design of the early shrinkage-deformation properties and mechanical properties of gradient-structured composites under extreme environments as well as the assessment of service life.